An epidemiological cross-sectional study to assess the socio-demographic profile and to study the prevalence of overweight and obesity among adults in an urban slum of Mumbai - Saji, Daniel A.; Jajulwar, Mahesh B.; Shenoy, Anita G. (International Journal Of Community Medicine And Public Health, 2017)
Background: Obesity is perhaps the most prevalent form of malnutrition. As a chronic disease, prevalent in both developed and developing countries, and affecting both children and adults. In India due urbanization and modernization people are moving into urban centres and along with increasing wealth, concerns about an obesity epidemic in India are growing. The present study was carried out to assess the demographic distribution and prevalence of overweight and obesity in adults in an urban slum. Methods: The cross sectional study includes 350 adult populations from the Shivaji Nagar (Govandi) urban slum of the Mumbai city in India and study was carried out over a period of one year from August 2014 to July 2015. Results: Our study showed that most of subjects are in the age group of 38-57. Sex distribution was relatively equal with 44% males and 56% females. Majority of the population were Muslims. Majority of the subjects (50.6%) belong to class III, (26.9%). 32.3% subjects were obese and 8.6% were overweight according to BMI (basal metabolic index) while merely 6.6% were overweight according to WHR (waist to hip ratio). Thus BMI was found to be a better indicator than WHR for measuring obesity. Conclusions: From the present study it was seen that age group of the subjects, socio economic class, and level of education had a significant relationship with BMI, whereas sex of the subjects had non-significant relationship with BMI.